Progressive accumulation of cytoplasmic aggregates in PRPF31 retinal pigment epithelium cells interferes with cell survival - Maria Georgiou; Robert Atkinson; Sina Mozaffari‐Jovin; Majlinda Lako (Wiley, 2022)
Abstract Retinitis Pigmentosa (RP) is a common form of inherited degenerative disease that often leads to blindness. About 10% autosomal dominant RP cases have been associated with mutations in PRPF31 gene, which is involved in pre‐mRNA splicing. This commentary summarises the key findings of our recent publication 'Activation of autophagy reverses progressive and deleterious protein aggregation in PRPF31 patient‐induced pluripotent stem cell‐derived retinal pigment epithelium cells' in the context of large cytoplasmic aggregates which accumulate progressive with time and impair cell function and survival. Understanding the pathomechanism of PRPF31‐RP provides invaluable information that can be used to understand other PRPF‐RPs, and help to design effective and appropriate therapeutic strategies for the treatment of RP patients with PRPF31 mutations.